Firm performance, corporate governance and CEO compensation in Chinese Growth Enterprise Market - Chen, Siqi (2020)
Most previous studies focus on the Chief Executive Officer (CEO) compensation are based on the experience of developed countries. There is less research on developing countries. Therefore, this study focuses on China which is a developing country with rapid economic development. Since Growth Enterprise Market companies of China newly revised relevant regulations on the disclosure of executive compensation in 2014, there is no study analysing the relationship between CEO compensation, performance and corporate governance in GEM companies after the revised regulations. Therefore, this study will try to make up for the research gap. This study takes Chinese Growth Enterprise Market companies as the sample to study the relationship between firm performance, corporate governance and CEO compensation. The data of 394 companies listed in Chinese GEM from 2015 to 2018 are used. Based on the previous research, this study uses a fixed-effect panel data model to analyse the collected data. The research results show that performance is one of the main factors that determine CEO compensation. CEO duality has a significant negative influence on CEO compensation, which means that dual-CEO will not increase their salary. In this study, we also examined some other variables, such as the board size and the proportion of non-executive directors. However, these two variables have no significant relationship on the CEO compensation of GEM companies in China.